COP-30 AND THE FUTURE OF CLIMATE GOVERNANCE: BRAZIL’S ROLE IN THE TRANSITION TO SMART AND RESILIENT CITIES UNDER THE GIS CYCLE - Cavalcante, Ailton Ferreira (Seven Editora, 2025)
The COP-30, to be held in Belém (Brazil), represents a milestone in global climate governance by placing the Amazon at the center of international decision-making on mitigation, adaptation, and climate justice. Considering the strategic relevance of the event and the institutional challenges related to Brazil’s ability to implement its climate commitments, this study aims to examine how COP-30 may strengthen the transition towards smart and resilient cities, based on the theoretical framework of the GIS Cycle, Governance, Innovation, and Sustainability. The research adopts a qualitative approach grounded in documentary analysis of official national and international instruments, as well as recent Brazilian experiences involving digital and sustainable governance at the municipal level. The results demonstrate that Brazil has the potential to assume a leadership role in climate governance, provided that implementation, monitoring, and multilevel coordination capacities are reinforced. Additionally, the empirical focus on Belém and its strategic connection with Goiânia reveals opportunities to integrate climate diplomacy with local public policy. It is concluded that the GIS Cycle offers institutional conditions to transform climate ambition into concrete outcomes, enhancing the legacy of COP-30 for Brazilian territories and society. DOI: https://doi.org/10.56238/sevened2025.036-079